Analisis Kebutuhan Pelatihan Berbasis Kompetensi untuk Meningkatkan Kinerja Sales Promotion Girl/Boy (Spg/Spb) di Matahari Departement Store Balikpapan - Tresnawati Tresnawati; Alif Muallim (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Human Resource Management plays a crucial role in enabling companies to manage, organize, and utilize their workforce effectively, productively, and efficiently in order to achieve organizational goals. Human Resources (HR) represent one of the most important factors for PT Matahari Department Store Balikpapan, as employees significantly influence the company’s success in achieving operational targets and long-term business development plans. This study aims to describe the implementation of competency-based training for Sales Promotion Girls (SPGs) at PT Matahari Department Store Balikpapan. The research employs a qualitative approach to gain an in-depth understanding of the training process. Data were collected through direct interviews with selected informants within the company, supported by relevant documentation. The findings show that the implementation of competency-based SPG training at PT Matahari Department Store Balikpapan is conducted systematically through several structured stages, including open recruitment, administrative selection, interviews, and training sessions. These stages are designed to ensure that employees possess the required competencies and are placed in appropriate positions. Overall, the training process contributes positively to improving workforce quality, employee performance, and the effectiveness of staffing within the organization.